PENGARUH EFIKASI DIRI DAN TINGKAT RELIGIUSITAS TERHADAP KECURANGAN AKADEMIK MAHASISWA FKIP UNS - Ichsan, Muhammad Chaerul; Muhtar, Muhtar (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
This research aims to examine: (1) the influence of self-efficacy on academic cheating of FKIP UNS students, (2) the influence of the level of religiosity on academic cheating of FKIP UNS students, (3) the influence of self-efficacy and level of religiosity on academic cheating of FKIP UNS students. This type of research is causal quantitative research. The population in this study were all students from the 2021 class of FKIP UNS, Kentingan campus with a total sample of 313 respondents. The data collection technique in this research uses a questionnaire. The research results show: (1) there is a negative influence of self-efficacy on academic cheating of FKIP UNS students as evidenced by the t test results of 2.093 > 1.649 and a significance value of 0.037 < 0.05. (2) there is a negative influence of the level of religiosity on FKIP UNS students' academic cheating as evidenced by the t test results of 9.642 > 1.649 and a significance value of 0.000 < 0.05. (3) there is a joint negative influence between self-efficacy and the level of religiosity on academic cheating of FKIP UNS students as evidenced by the F test results of 95.271>2.63 and a significance value of 0.00<0.05.